2013
DOI: 10.1016/j.molimm.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The Ras GTPase-activating protein neurofibromin 1 promotes the positive selection of thymocytes

Abstract: TCR-mediated activation of the Ras signaling pathway is critical for T cell development in the thymus and function in the periphery. However, which members of a family of Ras GTPase-activating proteins (RasGAPs) negatively-regulate Ras activation in T cells is unknown. In this study we examined a potential function for the neurofibromin 1 (NF1) RasGAP in the T cell lineage with the use of T cell-specific NF1-deficient mice. Surprisingly, on an MHC class I-restricted TCR transgenic background, NF1 was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
3
21
1
Order By: Relevance
“…However, the frequency of lymphocytes and monocytes expressing pro-inflammatory and Th1 cytokines was decreased in NF1 patients compared with controls, whereas the frequency of T lymphocytes expressing anti-inflammatory and Th2 cytokines was increased. In contrast to our results, another study showed that the secretion of cytokines appeared unchanged in T cells of NF1-deficient mice (Oliver et al, 2013). The main Th2 cytokine, IL-4, is an important cytokine for the initiation and effectiveness of Th2 immune reactions, such as allergic immune processes and tissue remodeling (Wang and Joyce, 2010).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the frequency of lymphocytes and monocytes expressing pro-inflammatory and Th1 cytokines was decreased in NF1 patients compared with controls, whereas the frequency of T lymphocytes expressing anti-inflammatory and Th2 cytokines was increased. In contrast to our results, another study showed that the secretion of cytokines appeared unchanged in T cells of NF1-deficient mice (Oliver et al, 2013). The main Th2 cytokine, IL-4, is an important cytokine for the initiation and effectiveness of Th2 immune reactions, such as allergic immune processes and tissue remodeling (Wang and Joyce, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…We observed that the frequency of CD4 + (but not CD8 +) T cells was decreased in NF1 patients compared to controls. In a recent study by Oliver et al (2013), numbers of naïve CD4 + and CD8 + T cells were shown to be peripherally decreased in T cell-specific NF1-deficient mice but NF1 was dispensable as a regulator of TCR-induced Ras activation and cell proliferation. Despite our work did not evaluate the naïve phenotype or the influence of NF1 as a regulator of cell proliferation and activation results showed that the frequency of CD4 + T cells was decreased in NF1 patients compared to controls.…”
Section: Discussionmentioning
confidence: 98%
“…Non-conditional gene knockout mice lacking expression of either RASA1 or NF1 die in mid-gestation as a result of abnormal cardiovascular development (810). Therefore, to investigate the roles of RASA1 and NF1 in the T cell compartment, we had previously generated T cell-specific NF1 and RASA1-deficient mice (11, 12). RASA1 and NF1 were found to be largely dispensable for normal T cell development in non-TCR transgenic mice, although subtle alterations in the efficiency of thymocyte positive selection were apparent on TCR transgenic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…In culture, both Nf1 −/− and Nf1 −/+ thymocytes as well as mature splenic T cells proliferate less after IL-2 and CD3 stimulation than wildtype [84,86], whereas unstimulated proliferation of Nf1 −/+ thymo cytes is increased compared with wild-type. Loss of Nf1 in maturing T cells leads to inhibition of positive selection in the context of MHC class I restricted T-cell receptor transgenic mice and fewer naive T cells in the spleen [85]. These data suggest that the effect of Nf1 mutation on T cells is very specific to different stages of T-cell maturation and stimulation, and may depend on Nf1 mutation in other cells of the immune compartment.…”
Section: • T Cellsmentioning
confidence: 81%
“…Bone marrow transplant of Nf1 null cells into immune compromised mice results in increased thymic cellularity. Targeted loss of Nf1 in maturing T cells did not lead to increased thymic cellularity, so this effect may be due to interactions between different cell types in the thymus [85]. In culture, both Nf1 −/− and Nf1 −/+ thymocytes as well as mature splenic T cells proliferate less after IL-2 and CD3 stimulation than wildtype [84,86], whereas unstimulated proliferation of Nf1 −/+ thymo cytes is increased compared with wild-type.…”
Section: • T Cellsmentioning
confidence: 97%